Cover Image, Volume 89, Issue 6. (19th November 2018) - Liu, Wei; Zhang, Qian‐Yue; Yuan, Fei‐Fei; Wang, Hai‐Ning; Zhang, Le‐Le; Ma, Yu‐Ru; Ye, Xiao‐Ping; Zhang, Man‐Man; Song, Zhi‐Yi; Li, Sheng‐Xian; Du, Wen‐Hua; Liang, Jun; et al.
Abstract : The cover image is based on the Original Article A dense mapping study of six European AITD susceptibility regions in a large Chinese Han Cohort of Graves' disease by Wei Liu et al., DOI:10.1111/cen.13847 . Design Credit: Qianyue Zhang.